Lanthanide complexes that respond to changes in cyanide concentration in water - Routledge, J; Zhang, X; Connolly, M; Tropiano, M; Blackburn, O; Kenwright, A; Beer, P; Aldridge, S; Faulkner, S (Wiley, 2017)
Cyanide ions are shown to interact with lanthanide complexes of phenacylDO3A derivatives in aqueous solution, giving rise to changes in the luminescence and NMR spectra. These changes are the consequence of cyanohydrin formation, favoured by the coordination of the phenacyl carbonyl group to the lanthanide centre. These complexes display minimal affinity for fluoride and can detect cyanide at <1 µM concentrations. By contrast, lanthanide complexes with DOTAM derivatives display no affinity for cyanide in water, but respond to changes in fluoride concentration.